Peningkatan Kompetensi Penyuluh Kehutanan Lingkup Sulawesi melalui Pelatihan Penyusunan Materi dan Pembuatan Media Penyuluhan Tercetak - Adi Riyanto Suprayitno (Institut Pertanian Bogor, 2019)
Community empowerment is the task of forestry extension workers. In order for forestry extension activities to run well, the media is needed as a tool, one of which is printed media. The existence of printed media for extension can facilitate forestry extension agents in disseminating information that can invite farmers to be involved in community empowerment activities. Therefore, mastery of the competence of making printed media is a necessity for forestry extension workers. The purpose of this training was to increase the knowledge and skills of the forestry extension workers in Sulawesi on writing materials and making extension media printed in the form of brochures, leaflets, folders, and posters. Through training in the preparation of materials and the creation of printed extension media, forestry extension workers are provided with knowledge and skills on how to make printed extension media. The training learning process uses brainstorming methods, interactive lectures, question and answer, discussion, and assignments/practices. The results of the study showed that there were increasing in participants' knowledge and skills after they attended the training which were proven by producing quite good printed media drafts.